Kondisi Fisik dan Teknik Dasar Siswa SMPN 6 Yogyakarta pada Ekstrakurikuler Bola Basket Putra - Octaviasari, Novi; Tomoliyus, Tomoliyus; Sukamti, Endang Rini (Fakultas Pendidikan Olahraga dan Kesehatan, Universitas Pendidikan Indonesia, 2024)
Basketball is a team sport that has 10 players in one team, with basic movements, especially shooting. Shooting in handball is a form of attack aimed at producing points and weapons to win a match. This study aims to determine the level of physical condition and basic techniques of students at SMP N 6 Yogyakarta in extracurricular men's basketball. The research subjects were 10 men's basketball extracurricular students at SMP N 6 Yogyakarta. The method used in this research is quantitative descriptive using survey methods. Based on the results of research on the level of physical condition and basic techniques of students at SMP N 6 Yogyakarta, namely the level of physical condition of men's basketball extracurricular students at SMP N 6 Yogyakarta in the very good category was 1 student (10%), good was 1 student (10%), fair as many as 5 students (50%), less than 2 students (20%), very less as 1 student (10%) then, the level of basic technical ability of men's basketball extracurricular students at SMP N 6 Yogyakarta in the very good category was 0 students ( 0%), good as many as 4 students (40%), fair as many as 5 students (50%), poor as many as 0 students (0%), very poor as many as 1 student (10%). The above results can be interpreted as saying that the level of physical condition of the men's basketball extracurricular students at SMP N 6 Yogyakarta is mostly in the adequate category, then the level of basic technical ability of the men's basketball extracurricular students at SMP N 6 Yogyakarta is mostly in the adequate category.